2014
DOI: 10.1590/s1415-43662014000700001
|View full text |Cite
|
Sign up to set email alerts
|

Desenvolvimento inicial do milho submetido à adubação com manipueira

Abstract: R E S U M OObjetivou-se, com este estudo, verificar o efeito da adubação utilizando manipueira no desenvolvimento inicial do milho. O experimento foi conduzido em ambiente protegido na UFRPE, Recife, PE. Os tratamentos constaram de um arranjo fatorial 5 x 3, sendo 5 doses de manipueira equivalentes a: 0; 12,6; 25,2; 50,4 e 75,6 m 3 ha -1 e 3 idades de corte: aos 20, 40 e aos 52 dias após a germinação -DAG, com quatro repetições, em delineamento inteiramente casualizado. Utilizou-se um híbrido de milho forragei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 13 publications
1
11
0
7
Order By: Relevance
“…Ambiental, v.21, n.10, p.681-685, 2017. Magalhães et al (2014) reported an increase in the stem diameter with lower cassava effluent doses, and a decrease with increased doses; for example, they observed a decrease at the dose of 63 m 3 ha -1 . In addition, they reported an adverse effect on the absorption of other elements, such as calcium, magnesium, zinc, and manganese by the plant, if they are present in excess, possibly because of the high concentration of the potassium ion in the effluent (Malavolta et al, 1997).…”
Section: Bmentioning
confidence: 99%
See 2 more Smart Citations
“…Ambiental, v.21, n.10, p.681-685, 2017. Magalhães et al (2014) reported an increase in the stem diameter with lower cassava effluent doses, and a decrease with increased doses; for example, they observed a decrease at the dose of 63 m 3 ha -1 . In addition, they reported an adverse effect on the absorption of other elements, such as calcium, magnesium, zinc, and manganese by the plant, if they are present in excess, possibly because of the high concentration of the potassium ion in the effluent (Malavolta et al, 1997).…”
Section: Bmentioning
confidence: 99%
“…Dantas et al (2015) evaluated the growth of sunflower using cassava effluent and found that the factors related to plant growth increased with greater applied doses of this effluent. Magalhães et al (2014) investigated the use of the same effluent to promote the development of corn, confirming that it can be used as a source of fertilizer whose efficiency depends on the use of appropriate doses of the residue.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Considering the agro-industrial development and generation of large amounts of organic residues with high polluting potential to the environment (330 million tons, on average) along the productive chain of various products, the reuse of these residues in agriculture has been considered as one way to attenuate the environmental impacts inherent to their disposal in the environment, besides pointing to a new, promising use of these residues (Morais et al, 2012;Virmond, 2011;Damasceno et al, 2003;Magalhães et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Authors such as Barreto et al (2014) and Magalhães et al (2014) evaluated the effects of using cassava waste-water as source of nutrients in agricultural production and observed significant results up to a certain volume threshold. Akpan-Idiok et al (2012) and Araújo et al (2015) observed increments in plant green matter applying human urine through irrigation.…”
Section: Introductionmentioning
confidence: 99%